Social representations of call and vocation among Portuguese evangelical Christians: an exploratory study - Arabis, Thomas (European journal of theology, 2015)
This study traces the contours of the social representations of the concepts of call and vocation in the Portuguese evangelical community, using four questions: 1) Do the terms represent two realities or one? 2) Do they represent a universal experience or are they limited to certain individuals? 3) Do they offer generic orientation or individualised and particularised guidance? 4) Is one esteemed more highly than the other? Following the description of the social representations, a brief analysis of the biblical data concerning the concept is offered as a means of highlighting variances between the two. The article concludes with implications derived from the study.